Chromatographie Sur Couche Mince Et Activité Antiradicalaire D’extraits De Pupalia Lappacea (L.) Juss. Amaranthaceae - Jazy, Mamadou Aïssa; Rokia Sanogo, Mahamane Haïdara (European Scientific Journal, ESJ, 2018)
Introduction: P. lappacea is a plant used in traditional medicine, in the regions of Niamey and Tillaberi, as anti-hemorrhoids. It contains tannins, sterols, triterpenes, saponosides, mucilages, anthracene derivatives, oses and holosides for which it is necessary to appreciate the activities relating to the medicinal virtues. Objective: To contribute to the phytochemical and pharmacological study of Pupalia lappacea, through the semi-quantitative estimation of phytocomposés and the research of the antiradical power of its various extracts. Methodology: Phytochemical screening, semiquantitative estimation and a study of the antioxidant activity of phytocomposites were carried out by thin layer chromatography (TLC) from extracts obtained with increasing polarity solvents. Results: All P. lappacea extracts contain a large number of bioactive chemical compounds. Substances with antihaemorrhoidal activity (phenolic compounds, tannins) are found mainly in the aqueous extracts (digested, decoct exhausted) and the methanolic extract. The strongest antiradical activity observed with the digest and the spent decoction after migration in the solvent system. Ethyl acetate - Methyl ethyl ketone - Formic acid - Water (5-3-1-1) would be linked to phenolic compounds. A less severe free radical activity, probably due to terpenic substances, was observed with the BAW solvent system (60-15-25). The extract corresponding to the traditional (decocted) use of P. lappacea also has low antioxidant activity. Conclusion: The use of P. lappacea as antihemorrhoid is justified. However, the digest and the spent decoction would have greater anti-hemorrhoidal properties than those of the decoction obtained by the traditional method. An assay of the phenolic compounds, tannins, terpenic compounds, in the infused, the decoction, the digested and the exhausted decoction would make it possible to choose the best method of extraction and to improve the anti-hemorrhoidal effect of the P. lappacea based medicinal preparations.